Handbook of Pyrrolidone and Caprolactam Based Materials 2021
DOI: 10.1002/9781119468769.hpcbm013
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Behavior of Polylactam Clathrate Hydrate Inhibitors and theirSmall‐MoleculeModel Compounds

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…These groups have hydrophilic parts that have strong hydrogen bonding properties such as amide, imide, or amine oxide, although many other functional groups have been investigated. Well-known examples of KHI polymers include homo- or copolymers of N -vinyl caprolactam (VCap), N -vinylpyrrolidone (VP), and N -isopropylmethacrylamide (NIPMAm) (Figure ). The homopolymer of VCap, PVCap, is a powerful KHI and is often used as a standard to gauge the performance of other polymers . PVCap is a thermoresponsive polymer in aqueous solution, meaning that it becomes insoluble above a specific temperature. , For PVCap, this lies at about 30–45 °C depending on the polymerization method, which can affect parameters such as molecular weight, endcapping, tacticity, and branching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These groups have hydrophilic parts that have strong hydrogen bonding properties such as amide, imide, or amine oxide, although many other functional groups have been investigated. Well-known examples of KHI polymers include homo- or copolymers of N -vinyl caprolactam (VCap), N -vinylpyrrolidone (VP), and N -isopropylmethacrylamide (NIPMAm) (Figure ). The homopolymer of VCap, PVCap, is a powerful KHI and is often used as a standard to gauge the performance of other polymers . PVCap is a thermoresponsive polymer in aqueous solution, meaning that it becomes insoluble above a specific temperature. , For PVCap, this lies at about 30–45 °C depending on the polymerization method, which can affect parameters such as molecular weight, endcapping, tacticity, and branching.…”
Section: Introductionmentioning
confidence: 99%
“…The homopolymer of VCap, PVCap, is a powerful KHI and is often used as a standard to gauge the performance of other polymers. 16 PVCap is a thermoresponsive polymer in aqueous solution, meaning that it becomes insoluble above a specific temperature. 17 , 18 For PVCap, this lies at about 30–45 °C depending on the polymerization method, which can affect parameters such as molecular weight, endcapping, tacticity, and branching.…”
Section: Introductionmentioning
confidence: 99%
“…PVCap is still well known as one of the strongest KHI polymers and HCGI. PVCap is a commercially available water-soluble polymer of 7-ring N -vinyllactam. Quaternary ammonium salts (quats) are weak KHIs yet can act as HCGIs on structure II (sII) gas hydrate. Quats can be synergists for KHI polymers such as PVCap on both tetrahydrofuran (THF) and sII gas hydrate. Typical quats are tetrapropylammonium bromide (TPrAB) and tetrapentylammonium bromide (TPeAB). The THF hydrate growth inhibition effect of TPeAB is stronger than that of TPrAB.…”
Section: Introductionmentioning
confidence: 99%
“…A representative KHI is a series of N -vinyllactams. The first breakthrough in KHI technology is poly­( N -vinylpyrrolidone) (PVP), which was investigated by the Colorado School of Mines (CSM) in 1991. , In a subsequent study, the CSM found that poly­( N -vinylcaprolactam) (PVCap) had better inhibition performance than PVP . PVCap is still well known as one of the strongest KHI polymers and HCGI.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence that some polymers can melt or prevent hydrate formation indefinitely a few degrees Kelvin within the hydrate-stable region . Although many classes of chemicals have been proposed as KHIs, all commercial KHIs are based around water-soluble polymers with amphiphilic groups as the main active ingredient. Most of these polymers are vinylic polymers, based on amide monomers including N -vinylpyrrolidone (VP), N -caprolactam (VCL), and N -isopropylmethacrylamide (NIPMAm) (Figure ).…”
Section: Introductionmentioning
confidence: 99%